Funkcionalʹnaâ stilistika v ee otnošenii k èstetičeskomu idealizmu : v vozmožny li elementy sinteza? - Salimovskij, Vladimir A. (Stylistyka, 2021)
In the history of theoretical stylistics traditional and creative aspects of culture were di vi- ded between two branches of science: functional stylistics and aesthetic idealism. Never- theless developing of functional stylistics has led to integration with idealism. The ten- dency occurs in the interest to the individual style of a writer, a joumalist, a scientist. We also can see this tendency in the interpretations of the concepts “expressivity” and “text style” and in the search for the driving force of linguistic transformations. The possibility of integration depends on progress in the psychology of creativity at the understanding of aesthetic idealism’ concepts. Elements of the synthesis in representations of these two branches contribute to the investigation of the generał problems of Humanities, such as the relationship of social and individual, traditional and innovative.